Sexsation and the Neo-New Woman in Sarah Waters’s Fingersmith (2002) - Lilia Louati (Études Britanniques Contemporaines, 2022)
Marie-Luise Kohlke’s concept of neo-Victorian ‘sexsation’ characterises the project of contemporary novelist Sarah Waters to explore sensational representations of the Victorians’ sexual lives. In Fingersmith, Waters re-imagines patriarchal Victorian pornography rife with masculine stereotypes of male domination and female subjugation embodied in the pornographic archive of Mr Lilly. Subverting the structures of subjugation, however, she describes Maud and Susan’s own discovery of lesbian sexuality; a sexual awakening accompanied with Maud’s journey towards literary creativity for she eventually emerges as a writer of erotica in her own right, thus recalling New Woman figures of the 1890s. The aim of this essay will be first to explore how such a sexsational narrative enables a radical revision of patriarchal discourses on sexuality. Then we shall examine to what extent Waters’s plot of lesbian creativity is indebted to the artist’s novel of the 1890s and to the late-Victorian New Woman novel. With its emphasis on ‘dissident’ sexualities and woman’s emancipation through writing, can Waters’s Fingersmith be considered as neo-New Woman fiction?